Avaliação da Hipertensão porta em crianças e adolescentes com obstrução extra-hepática da Veia Porta - Ana Paula Pereira de Oliveira (2018)
Extrahepatic portal vein obstruction (EHPVO) is characterized by obstruction of the extrahepatic portion of the portal vein, with or without involvement of the intrahepatic portion or superior splenic or mesenteric veins. Bleeding from esophageal varices is one of the main consequences of portal hypertension resulting from EHPVO. This study aims to describe the characteristics of children and adolescents with EHPVO, followed at the pediatric hepatology service of Hospital das Clínicas da UFMG. The endoscopic and clinical factors associated with upper gastrointestinal bleeding (UGB) and the results of primary and secondary endoscopic prophylaxis to which these patients were submitted during follow-up were evaluated. We included 72 patients, 51.4% of the male gender. The initial clinical manifestation in 48.6% of these patients was splenomegaly with hypersplenism, followed by UGB in 43%. Fifty patients had some episode of bleeding during follow- up, with median age of first bleeding of 4.81 years (Q1;Q3: 2.09; 7.34). Patients were divided into 2 groups for the comparison of the risk factors associated with the initial episode of bleeding, and 64 patients who had complete data from the first endoscopy were analyzed. After multivariate analysis, it was found that the esophageal varices of medium and large size are associated with the risk of bleeding, with an Odds Ratio of 18, confidence interval (2.5%-97.5%) of 4.33-74.76 and a p<0.0001. Primary prophylaxis was performed in 14 patients through elastic band ligation, with esophageal varices eradication in 85.7%, with a median of 3.5 sessions to eradicate. Bleeding occurred in 14.3% and recurrence of esophageal varices in 41.7% . Secondary prophylaxis was performed in 41 patients, 58.5% of whom with sclerotherapy. There was eradication of varices in 90.2% of the cases, with a median of 4 sessions. There was recurrence and rebleeding of esophageal varices in 45.9% and 34.1% of the children, respectively. In this study, varices of medium and large size were associated with the risk of bleeding in patients with EHPVO, with a 18 times greater chance of bleeding. The type of study performed and the limited size of the sample do not allow definitive extrapolations or conclusions, although they follow the same trend of studies in cirrhotic patients. By restoring the flow in the portal vein, the meso-Rex shunt is considered a better approach in EHPVO. However, not all patients have an anatomy that allows the surgery to be performed, and it requires an experienced staff and a structure that is not available in all services. Studies evaluating the endoscopic approach to primary and secondary prophylaxis of bleeding and investigating the risk factors for its occurrence are important for better management of patients in whom surgery is not possible.